ORKES SIMFONI DALAM PERSPEKTIF HABITUS BOURDIEU - Susilo, Y. Edhi (Jurnal Kawistara, 2014)
Symphony orchestra in Indonesia according to the perspective of âhabitus Bourdieuâ has managed tocreate a middle-class symphony orchestra music. Habitus is in the process of producing and reproducingthe group, and when the group was awakened, finally realizing that he is a group. The existence ofa symphony orchestra in Indonesia was pioneered by Radio Orchestra and Orchestra Studio in RRIJakarta in 1950. In 1966 on the initiative of Ali Sadikin, both the orchestra and being joins with nameOrkes Simfoni Jakarta (OSJ). OSJ as outset of symphony orchestra in Indonesia, further influencingthe emergence of various symphony orchestras such as: University of Indonesia Symphony Orchestra(1983), Twilite Orchestra (1991), Surabaya Symphony Orchestra (1996), Nusantara Symphony Orchestra(2000), Gita Bahana Nusantara (2003 ), and others.